Discovery Learning Pada Pembelajaran Biologi Konsep Pencemaran Lingkungan - Hidayat, Rafi Nur; Rasyid, Abdur; Mu'minah, Iim Halimatul (Publisher by: Papanda Publisher, 2023)
The purpose of this study was to examine the literature on discovery learning models on environmental pollution material on student learning outcome. Data collection is done by collection related books and journals for later reading dan review. In addition to the collected data, testing and comparison of the data found was carried out. The data analysis technique was carried out qualitatively by quoting the appropriate opinion. The results showed that the discovery learning model is a good model used in learning environmental materials on student learning outcomes. This can be seen from the many learning theories that support the discovery learning model.